2020
DOI: 10.1083/jcb.201908036
|View full text |Cite
|
Sign up to set email alerts
|

Nesprins are mechanotransducers that discriminate epithelial–mesenchymal transition programs

Abstract: LINC complexes are transmembrane protein assemblies that physically connect the nucleoskeleton and cytoskeleton through the nuclear envelope. Dysfunctions of LINC complexes are associated with pathologies such as cancer and muscular disorders. The mechanical roles of LINC complexes are poorly understood. To address this, we used genetically encoded FRET biosensors of molecular tension in a nesprin protein of the LINC complex of fibroblastic and epithelial cells in culture. We exposed cells to mechanical, genet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 57 publications
(91 reference statements)
5
35
0
5
Order By: Relevance
“…In particular, as our electron microscopy data strongly suggest that adhesion between basal keratinocytes and the basal lamina remains normal in Sun dKO animals, we strongly favor this direct model ( Figure 6 ). Of note, cells migrating through constrictions or plated at high versus low packing density display lower tension on a distinct Nesprin TSMod variant similar in design to the one described here, suggesting that tension on the LINC complex may respond to a number of mechanical inputs depending on the experimental system ( Déjardin et al, 2020 ). However, high tension on the LINC complex at the edge of cell monolayer upon wounding compared to the interior of the monolayer ( Déjardin et al, 2020 ) is in line with the integrin dependence observed in this study.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In particular, as our electron microscopy data strongly suggest that adhesion between basal keratinocytes and the basal lamina remains normal in Sun dKO animals, we strongly favor this direct model ( Figure 6 ). Of note, cells migrating through constrictions or plated at high versus low packing density display lower tension on a distinct Nesprin TSMod variant similar in design to the one described here, suggesting that tension on the LINC complex may respond to a number of mechanical inputs depending on the experimental system ( Déjardin et al, 2020 ). However, high tension on the LINC complex at the edge of cell monolayer upon wounding compared to the interior of the monolayer ( Déjardin et al, 2020 ) is in line with the integrin dependence observed in this study.…”
Section: Discussionmentioning
confidence: 68%
“…In the N2G-JM-TSMod construct, the TSMod lies between the transmembrane domain and the entire cytosolic domain of mini-Nesprin-2, which contains both the N-terminal calponin homology domains that engage actin and a portion of the spectrin repeat region ( Figure 1A ). This construct is distinct from previously described Nesprin tension sensors in its design ( Arsenovic et al, 2016 ; Déjardin et al, 2020 ). We also generated a tension-insensitive construct by inserting the TSMod at the N-terminus of mini-Nesprin2 ( Figure 1A , ‘NoT_TSMod’) as well as ‘dark’ controls that allow for bleed through between fluorescence channels to be assessed ( Figure 1—figure supplement 1 ).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“… 46 , 47 Additionally, the LINC complex has a central role for mechanosensing and mechanotransduction, due to its function as a bridge between the cytoskeleton and the nucleus. 48 , 49 , 50 , 51 Nevertheless, how this LINC complex function is regulated as well as the different cellular processes where it is involved needs to be deciphered. The role of Ctdnep1-Eps8L2 interaction on actin organization described in this report can therefore be involved in the multiple functions of LINC complex-mediated nucleus-cytoskeleton connection.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that Arsenovic et al were first to insert the TSMod into mininesprin-2G, allowing them to demonstrate that nesprin-2G is subject to actomyosindependent tension and sensitive to cell elongation (7). They inserted TSMod in between SR2 and SR55 of mini-nesprin-2G (7), whereas Déjardin et al inserted it between SR56 and the transmembrane domain (2).…”
mentioning
confidence: 99%